Baseline risk of hematologic malignancy at initiation of frontline PARP inhibitor maintenance for BRCA1/2-associated ovarian cancer - Anastasia Navitski; Duaa H. Al-Rawi; Ying Liu; Maria M. Rubinstein; Claire F. Friedman; Raajit K. Rampal; Diana L. Mandelker; Karen Cadoo; Roisin E. O'Cearbhaill (Elsevier, 2021)
Poly(ADP-ribose) polymerase inhibitors (PARPi) are FDA approved as frontline maintenance for BRCA-associated advanced stage high-grade ovarian cancer (HGOC), having demonstrated an unprecedented improvement in relapse-free survival. Myelodysplastic syndrome (MDS) and acute myeloid leukemia (AML) are rare toxicities of PARPi. We describe three patients with germline BRCA-associated (gBRCA+) HGOC and alterations in AML driver genes. Although none evidenced overt hematologic malignancy, PARPi maintenance was cautiously considered given the potential risk of MDS/AML. A better understanding of the role of clonal hematopoiesis in the subsequent development of PARPi-associated MDS/AML will improve management of this patient population.